Ascorbate Reduces Mouse Platelet Aggregation and Surface P‐Selectin Expression in an Ex Vivo Model of Sepsis. (9th August 2013) - Secor, Dan; Swarbreck, Scott; Ellis, Christopher G.; Sharpe, Michael D.; Tyml, Karel
Abstract Objective Compromised perfusion of the capillary bed can lead to organ failure and mortality in sepsis. We have reported that intravenous injection of ascorbate inhibits platelet adhesion and plugging in septic capillaries. In this study, we hypothesized that ascorbate reduces aggregation of platelets and their surface expression of P‐selectin (a key adhesion molecule) in mice. Methods Platelets were isolated from control mice and subjected to agents known to be released into the bloodstream during sepsis (thrombin, ADP or U46619, thromboxane A2 analog). Platelet aggregation was analyzed by aggregometry and P‐selectin expression by flow cytometry. Results Platelet‐activating agents increased aggregation and P‐selectin expression. Ascorbate inhibited these increases. This inhibitory effect was NOS‐independent (LNAME had no effect). In contrast to the platelet‐activating agents, direct stimuli lipopolysaccharide, TNFα, or plasma from septic mice did not increase aggregation/expression, a finding consistent with the literature. The results suggest a complex mechanism of platelet aggregation and P‐selectin expression in sepsis, where generation of platelet‐activating stimuli is required first, before platelet aggregation and adhesion in capillaries occur. Conclusion The ability of ascorbate to reduce platelet aggregation and P‐selectin expression could be an important mechanism by which ascorbate inhibits capillary plugging in sepsis.